Speaking as the leading aspect in teaching english - Popovskaya, A. V.; Gordienko, V. M.; Поповська, Ганна Валеріївна; Гордієнко, Вікторія Михайлівна (Харківський національний автомобільно-дорожній університет, 2013)
Since language is a means of communication, teaching speaking is a prior task in any methodology. This article is devoted to the research of the main methods of teaching speaking. These methods are fully described and their importance and productivity are proved.
Говоріння як пріоритетний аспект у викладанні англійської мови
Keywords: foreign language; speaking activities; speaking skills; teaching speaking; communication; іноземна мова; розмовна діяльність; навики говоріння; навчання говорінню; розмова